Porous electrode green sheet and granulated powder for forming same

JP7643832B2Active Publication Date: 2025-03-11NORITAKE MACHINE TECHNO CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2020017831
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-02-05
Publication Date
2025-03-11
Estimated Expiration
2040-02-05

AI Technical Summary

Benefits of technology

【0014】 ここに開示されるグリーンシートの一好適例において、105℃における乾燥減量が1質量%以下である。このような構成のグリーンシートは、乾式法によっていわゆる溶剤レスで製造されたと考えることができる。この場合、組成のムラが抑制されて均一なグリーンシートが提供される。また、このようなグリーンシートは、環境負荷の少ない製法によるものである点において好ましいといえる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643832000002
    Figure 0007643832000002
  • Figure 0007643832000003
    Figure 0007643832000003
  • Figure 0007643832000004
    Figure 0007643832000004
Patent Text Reader

Abstract

To provide a green sheet for a porous electrode, which is improved in handleability, and granulated powder to form it.SOLUTION: A green sheet to be used for forming a porous electrode is provided according to the present invention. The green sheet comprises: a main material including an electrode-forming material and a pore-forming material; and an auxiliary material which is an organic component other than the pore-forming material, including a binder and a plasticizer. The green sheet has a tensile storage elastic modulus of 60 MPa or larger and 350 MPa or smaller at 30°C. It is preferred that the average ellipticity of sectional shapes of pores recognized on a sintered body produced by sintering the green sheet is 0.6 or larger on condition that the pore-forming material is spherical powder.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a green sheet for a porous electrode and a granulated powder for forming the same. [Background technology]

[0002] Solid oxide fuel cells (hereinafter referred to simply as "SOFCs") have one of the highest power generation efficiency among various types of fuel cells and can use a variety of fuels, so they are being developed as a next-generation power generation device with a low environmental impact. The essential structure of a single SOFC cell is a dense layered solid electrolyte made of an oxygen ion conductor, with a porous air electrode (cathode) formed on one side of the solid electrolyte and a porous fuel electrode (anode) formed on the other side. Among them, anode-supported SOFCs, in which a solid electrolyte layer and a cathode layer are formed in that order on an anode support layer, are widely used.

[0003] These porous electrodes are typically manufactured by a wet method. That is, first, a raw material slurry (including terms such as paste, ink, suspension, etc.) is prepared by dispersing powder of the electrode constituent material in an organic solvent containing a binder, and the slurry is applied to a substrate and dried to prepare a green sheet. Next, the green sheet is cut into an appropriate shape and fired to manufacture the desired porous electrode. Here, in recent years, a dry method has been proposed for manufacturing green sheets without using organic solvents and omitting the drying process, thereby producing green sheets with low environmental impact, energy saving, and low cost. For example, Patent Document 1 discloses a method of forming a green sheet by granulating a conductive powder and a binder and then roll-molding the granulated powder. It is described that the roll-molding method does not use an organic solvent, so that separation of the electrode constituent material and the binder, which have different specific gravities, does not occur, and a green sheet with high uniformity in composition and density can be obtained. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 6258882 Summary of the Invention [Problem to be solved by the invention]

[0005] In recent years, there has been a demand for stable production of high-quality SOFCs at low cost in order to popularize household fuel cell systems. However, green sheets for porous electrodes have potential issues such as insufficient durability against tensile stress and bending, and poor handling.

[0006] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a green sheet for a porous electrode having improved handling properties. Another object of the present invention is to provide a granulated powder that can suitably produce the green sheet. [Means for solving the problem]

[0007] According to the study of the inventors, when a green sheet for forming a porous electrode containing an electrode material and a pore-forming material is produced by a dry method, the rearrangement of the electrode material and the pore-forming material during compression is difficult to be smoothly performed due to the lack of a solvent. As a result, although a green sheet of homogeneous composition is obtained, it is found that the compressive stress is usually concentrated on the pore-forming material, which has a relatively large particle size and low strength compared to the electrode material, and the pore-forming material is compressed and deformed in the thickness direction in the green sheet and crushed flat. Then, it was found that such deformation of the pore-forming material brings about anisotropy in the physical properties of the green sheet, especially reducing the tensile properties in the direction parallel to the sheet surface, and that if such deformation of the pore-forming material can be suppressed by the organic components of the green sheet, the physical properties of the green sheet can be improved, and the present invention was completed.

[0008] That is, the green sheet used to form the porous electrode disclosed herein includes a main raw material containing an electrode constituent material and a pore-forming material, and an auxiliary raw material that is an organic component other than the pore-forming material and contains a binder and a plasticizer, and is characterized in that the tensile storage modulus at 30°C is 60 MPa or more and 350 MPa or less.

[0009] According to the above configuration, the main raw material containing the electrode constituent material and the pore forming material is mixed with the auxiliary raw material containing the binder and the plasticizer to be formed into a sheet. At this time, by appropriately adjusting the properties of the binder and the plasticizer, the 30°C tensile storage modulus of the green sheet is appropriately increased as described above. As a result, the green sheet has a moderately high elasticity and is not easily stretched or deformed by tensile stress. In addition, the green sheet is not too elastic, and resistance to bending deformation is not easily lost. As a result, the handling properties of the green sheet during cutting, transporting, and removal from the substrate are remarkably improved. As a result, the porous electrode can be formed stably with a good yield.

[0010] In a preferred embodiment of the green sheet disclosed herein, when the pore-forming material is a spherical powder, the average ellipticity of the cross-sectional shape of the pores confirmed in the sintered body obtained by sintering the green sheet is 0.6 or more. In other words, when a spherical pore-forming material is used, the average ellipticity of the cross-sectional shape of the pore-forming material contained in the green sheet is 0.6 or more. In this way, a green sheet in which the crushing of the pore-forming material is suppressed is preferable because it is easy to achieve the above-mentioned high tensile storage modulus and the anisotropy of the physical properties of the green sheet is mitigated.

[0011] In a preferred embodiment of the green sheet disclosed herein, the tensile strength is 0.6 MPa or more, and the tensile breaking strain is 4% or more. Also, the folding endurance is preferably 10 times or more. This provides a green sheet with high tensile strength and resistance to breaking due to tensile stress. Also, a green sheet with high resistance to folding is provided.

[0012] In a preferred embodiment of the green sheet disclosed herein, the ratio of the auxiliary material to the main material is 10 parts by mass or more and 17 parts by mass or less when the main material is 100 parts by mass. This is preferable because the organic components contained in the green sheet are appropriately increased, making it easier to achieve the above-mentioned storage modulus.

[0013] In a preferred embodiment of the green sheet disclosed herein, the binder preferably contains an acrylic polymer compound. This configuration allows a green sheet in which the binder component is easily burned through. The plasticizer preferably contains a diglycerin polymer. This configuration is preferable because it increases the elasticity of the binder and makes it easier to achieve the above-mentioned storage modulus.

[0014] In a preferred embodiment of the green sheet disclosed herein, the loss on drying at 105°C is 1% by mass or less. A green sheet having such a configuration can be considered to have been produced by a dry method without using a solvent. In this case, a uniform green sheet is provided with reduced compositional irregularities. In addition, such a green sheet is preferable in that it is produced by a method that places less of a burden on the environment.

[0015] In another aspect, the technology disclosed herein provides a granulated powder for forming a green sheet. The granulated powder is a powder formed by granulating a main raw material including an electrode-forming material and a pore-forming material, and an auxiliary raw material including a binder and a plasticizer, which is an organic component other than the pore-forming material. Preferably, the granulated powder disclosed herein has an average particle size of 10 μm or more and 200 μm or less. The granulated powder disclosed herein satisfies the following conditions: Roll temperature: equal to or higher than the softening point of the binder; Roll gap: 0.05~3.0mm; Molding speed: 0.5m / min; When a green sheet is formed by compressing the green sheet to a void ratio of 3% or less, the sheet has a tensile storage modulus at 30° C. of 60 MPa or more and 350 MPa or less.

[0016] The granulated powder disclosed herein is preferable in that a green sheet having improved handling properties can be produced in a dry process by roll compaction. [Brief description of the drawings]

[0017] [Figure 1] FIG. 2 is a diagram showing a schematic diagram of a process for producing a green sheet by a roll compaction method. [Diagram 2] FIG. 2 is a cross-sectional view illustrating a schematic diagram of a green sheet according to an embodiment. [Diagram 3] 1A is a cross-sectional SEM image of a sintered body of a green sheet of Example 3 and FIG. 1B is a cross-sectional SEM image of a sintered body of a green sheet of Comparative Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Hereinafter, preferred embodiments of the present invention will be described with reference to the drawings as appropriate. Note that matters other than those specifically mentioned in this specification and necessary for carrying out the present invention (e.g., the configuration and manufacturing method of SOFC) can be understood as design matters of a person skilled in the art based on the prior art in the relevant field. The present invention can be carried out based on the contents disclosed in this specification and the technical common sense in the relevant field. Note that in the following drawings, members and parts having the same function are described with the same reference numerals, and duplicated descriptions may be omitted or simplified. Also, the dimensional relationships (length, width, thickness, etc.) in each drawing do not reflect the actual dimensional relationships.

[0019] FIG. 1 is a schematic diagram showing a state in which a green sheet 10G is manufactured from raw material powder 1a using a roll molding machine 5. The granulated powder disclosed herein can be suitably used as the raw material powder 1a. The green sheet 10G used to form the porous electrode disclosed herein can be suitably manufactured by forming the granulated powder disclosed herein into a sheet shape by a roll compaction method, although this is not limited thereto. The green sheet 10G contains an electrode constituent material and a pore-forming material as main raw materials, and is fired to burn out the pore-forming material and sinter the electrode constituent material, thereby manufacturing a porous electrode. The granulated powder and the green sheet 10G will be described in detail below.

[0020] [Granulated powder] The granulated powder disclosed herein is prepared by granulating a main raw material containing an electrode-constituting material and a pore-forming material, and an auxiliary raw material containing a binder and a plasticizer. The granulated powder is typically prepared by mixing the main raw material and the auxiliary raw material in a substantially uniformly dispersed state and integrating them into a granular form. The granulated powder is typically prepared by mixing the main raw material and the auxiliary raw material and granulating them by a known granulation method.

[0021] The main raw materials include an electrode constituent material and a pore-forming material. The electrode constituent material may be various materials used to form the desired porous electrode. The electrode constituent material may be, for example, a powder of the material that essentially constitutes the electrode, or a powder of a precursor of the material. Hereinafter, the granulated powder disclosed herein will be specifically described, without being limited thereto, taking as an example a case in which the porous electrode is a fuel electrode of an SOFC.

[0022] The electrode constituent material of the SOFC fuel electrode includes a conductive material. As the conductive material, one or more of materials that exhibit electrical conductivity in the operating environment of the SOFC and have been conventionally used to form the fuel electrode of the SOFC can be used without any particular limitation. Specifically, metal materials such as titanium (Ti), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn), strontium (Sr), zirconium (Zr), ruthenium (Ru), palladium (Pd), osmium (Os), iridium (Ir), platinum (Pt), lanthanum (La), and gold (Au), as well as metal oxides thereof (hereinafter simply referred to as "metal-based materials") can be used. Among them, Co, Ni, Zr, Ru, cobalt oxide (CoO, Co2O3, Co3O4), nickel oxide (NiO, Ni2O3, Ni3O4), zirconium oxide (ZrO2), ruthenium oxide (RuO2), etc., which show reforming activity capable of directly steam reforming the supplied fuel, can be preferably used. Any one of these may be used alone, or two or more may be used in combination. In particular, Ni is relatively inexpensive compared to other metals and shows high reaction activity, so it can be a particularly suitable metal species. Therefore, in the granulated powder disclosed herein, nickel-containing materials (e.g., nickel or nickel oxide) can be particularly preferably used as the conductive material.

[0023] The electrode constituent material may be a composite material obtained by mixing a conductive material with another material. For example, a composite material obtained by mixing a conductive material with a solid electrolyte material (typically an oxide ion conductor) of SOFC described later at any ratio may be used. Suitable examples of the solid electrolyte material include stabilized zirconia such as yttria stabilized zirconia (YSZ), calcia stabilized zirconia (CSZ), and scandia stabilized zirconia (ScSZ). The solid electrolyte material may be one type or two or more types. The conductive material and the solid electrolyte material may be a mixture or may form a composite (for example, a cermet).

[0024] By mixing the conductive material and the solid electrolyte material in this way, when the fuel electrode layer and the solid electrolyte layer are laminated by co-firing, the compatibility (fit) between the green sheets can be improved, and the compatibility (for example, the thermal expansion coefficient harmony) between the fuel electrode layer and the solid electrolyte layer during firing can be improved. In addition, the bond (adhesion, airtightness) between the anode support layer and the solid electrolyte layer during operation of the SOFC can be improved. In other words, defects such as interface peeling can be suppressed from the formation of the green sheets to the operation of the SOFC obtained thereafter. In addition, a SOFC with excellent durability and reliability can be realized. The mixing ratio of the conductive material and the solid electrolyte material is not limited to this, but may be, for example, about 90:10 to 30:70 in mass ratio, preferably 80:20 to 40:60, and may be, for example, 50:50.

[0025] The properties of the electrode constituent material are not particularly limited, but for example, a powder (particulate) material having an average particle size of about 0.01 μm to 5 μm (typically 0.1 μm to 2 μm) can be preferably used. When preparing and using the above-mentioned cermet, materials having substantially the same average particle size may be mixed and used, or the conductive material, which is the binding metal component, may have a relatively smaller particle size than the solid electrolyte material, which is the ceramic component. As an example, it is preferable to mix a nickel-based material having an average particle size of about 0.1 to 1 μm (for example, 0.4 to 0.5 μm) and stabilized zirconia having an average particle size of about 0.4 to 1.5 μm (for example, 0.6 to 0.8 μm) in the above ratio. This makes it possible to form a green sheet with a more homogeneous composition. In this specification, the "average particle size" of the powder material refers to the particle size (D) corresponding to the cumulative 50% from the fine particle side in the volume-based particle size distribution measured by particle size distribution measurement based on a general laser diffraction / light scattering method. 50 The particle size can be adjusted by conventionally known methods such as pulverization, sieving, and classification.

[0026] As the pore-forming material, various materials can be used that are present in the green sheet when the green sheet is formed, and that can form pores by burning and disappearing when the green sheet is fired. Examples of such pore-forming materials include resin beads made of various resins, carbon powder, silicon carbide powder, silicon nitride powder, starch, etc. From the viewpoint of being lightweight and easy to form pores of a desired shape, resin beads can be preferably used. The composition of the resin beads is not particularly limited, and examples include acrylic resins, polyethylene resins, polypropylene resins, styrene resins, vinyl resins, etc. Although not limited thereto, from the viewpoint of good burn-through properties, it is preferable to use resin beads made of acrylic resins.

[0027] The shape of the pore-forming material is not particularly limited. From the viewpoint of not bringing about anisotropy in the physical properties of the green sheet, it is preferable that the shape is granular, polyhedral, spherical, etc., and a spherical or nearly spherical shape is more preferable. The size of the pore-forming material can be appropriately selected so as to realize the desired porous structure of the porous electrode. Typically, the average particle diameter of the pore-forming material is larger than the average particle diameter of the electrode constituent material. The average particle diameter of the pore-forming material may be, for example, 2 times or more, 4 times or more, for example, 6 times or more, or 8 times or more, of the average particle diameter of the electrode constituent material. However, if the average particle diameter of the pore-forming material is excessively large, it is not preferable in that the strength of the green sheet and the fired body is easily reduced. The average particle diameter of the pore-forming material may be, for example, about 20 times or less, or about 15 times or less, of the average particle diameter of the electrode constituent material. Such a pore-forming material is not limited to this, but for example, a powder (particulate) material having an average particle size of about 1 to 15 μm, typically about 2 to 10 μm, for example about 5 to 6 μm, can be preferably used.

[0028] The ratio of the electrode constituent material to the pore-forming material is not limited to this, but for example, the mass ratio can be approximately 80:20 to 99:1, and preferably approximately 85:15 to 95:5.

[0029] The auxiliary raw material is an auxiliary component for suitably forming the electrode constituent material and the pore-forming material into a sheet, and is an organic component in the granulated powder other than the pore-forming material. The auxiliary raw material includes a binder and a plasticizer. The auxiliary raw material may include various additives such as a dispersant, a release agent, an antifoaming agent, an antioxidant, and a thickener, as necessary.

[0030] The binder is a component for binding the particles of the electrode material and the pore-forming material to each other. The binder burns at a lower temperature than the pore-forming material and burns out. As the binder, various polymer compounds having binding properties can be used. Examples of such binders that can be used include cellulose-based polymer compounds such as methyl cellulose, ethyl cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxypropyl methyl cellulose, carboxymethyl cellulose, carboxyethyl cellulose, and cellulose acetate phthalate; ester-based polymer compounds such as methacrylic acid esters; acrylic-based polymer compounds such as polyvinyl alcohol, polyvinyl butyral, polymethyl methacrylate, polybutyl methacrylate, polymethyl acrylate, and polyethyl methacrylate; imide-based polymer compounds such as polyamide-imide and polyimide; ethylene-based polymer compounds such as polyethylene oxide; nitrile-based polymer compounds such as polyacrylonitrile and polymethallylonitrile; urethane-based polymer compounds such as polyurethane; vinyl-based polymer compounds such as polyethylene, polypropylene, polyvinylidene fluoride, polyvinylidene chloride polyvinyl fluoride, and vinyl acetate; latex-based polymer compounds such as styrene butadiene rubber; and epoxy-based polymer compounds such as bisphenol A-type epoxy resins, bisphenol F-type epoxy resins, novolac-type epoxy resins, and glycylamine-type epoxy resins. Among them, those that have thermoplasticity, are not decomposed by drying treatment (typically, heat treatment of about 100°C to 200°C), and are easily decomposed and removed by binder removal treatment (typically, heat treatment of about more than 200°C to 600°C) can be preferably used. As such a binder, an acrylic polymer compound or a material mainly composed of the acrylic polymer compound can be preferably used. Acrylic polymer compounds are also preferred in that they have high burn-out properties and can firmly bond particles of conductive material with a relatively small amount added.

[0031] As the acrylic polymer compound, various acrylic polymer compounds can be used without any particular limitation. For example, it may be a monomer mixture containing an alkyl (meth)acrylate as a main monomer (a component that accounts for more than 50% by weight of the total monomers) and further containing a sub-monomer copolymerizable with the main monomer. This monomer mixture may contain other copolymerization components in addition to the main monomer and the sub-monomer. Then, by copolymerizing these monomer mixtures, it can become an acrylic polymer compound having a predetermined function. In this specification, "(meth)acrylate" is a term meaning acrylate and methacrylate. Similarly, "(meth)acrylic" is a term meaning acrylic and methacrylic.

[0032] Examples of alkyl (meth)acrylates include those represented by the general formula: CH2=C(R 1 )COOR 2 In the above, a compound represented by the formula: 1 represents a hydrogen atom or a methyl group. 2 R represents a chain alkyl group having 1 to 20 carbon atoms. 2 is preferably an alkyl(meth)acrylate having a chain alkyl group with 1 to 14 carbon atoms, and more preferably an alkyl(meth)acrylate having a chain alkyl group with 1 to 10 carbon atoms, for example, 2 to 8 carbon atoms. 2 Preferred are alkyl (meth)acrylates in which the alkyl group is a butyl group or a 2-ethylhexyl group.

[0033] Examples of alkyl (meth)acrylates having a chain alkyl group having 1 to 20 carbon atoms include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and octyl (meth)acrylate. , isooctyl (meth)acrylate, nonyl (meth)acrylate, isononyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, tridecyl (meth)acrylate, tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, hexadecyl (meth)acrylate, heptadecyl (meth)acrylate, octadecyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, etc. These alkyl (meth)acrylates may be used alone or in combination of two or more. Although not particularly limited, preferred alkyl (meth)acrylates include, for example, n-butyl acrylate (BA) and 2-ethylhexyl acrylate (2EHA).

[0034] The secondary monomer has a function of introducing a crosslinking point into an acrylic polymer compound or controlling the binding property of the acrylic polymer compound, and a monomer component containing various functional groups can be used according to the desired binder properties. Such functional groups can be, for example, a carboxyl group, a hydroxyl group, an amide group, an amino group, an epoxy group, etc. Although not particularly limited, it is preferable to use an ethylenically unsaturated monomer having a hydroxyl group. The amount of the secondary monomer is not particularly limited, and can be appropriately designed so as to realize the desired adhesive layer properties. For example, from the viewpoint of achieving a good balance between the cohesive force and the adhesiveness of the polymer, the amount of the secondary monomer is, for example, 20 mass% or less in total, more preferably 15 mass% or less, for example 10 mass% or less, relative to 100 mass% of the alkyl (meth)acrylate. Note that other copolymerization components other than the secondary monomers exemplified here may be included. The ratio of the secondary monomer in the above monomer (total amount of the main monomer and secondary monomer) may be appropriately selected according to the desired degree of crosslinking, and can be, for example, about 1 to 10 mass% relative to 100 mass% of the total monomer components. The method for polymerizing the monomer mixture is not particularly limited, and any of the conventionally known general polymerization methods (emulsion polymerization, solution polymerization, etc.) can be used.

[0035] Preferred examples of the hydroxyl group-containing monomer include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, 12-hydroxylauryl (meth)acrylate, and [4-(hydroxymethyl)cyclohexyl]methyl acrylate. A particularly preferred example is 2-hydroxyethyl methacrylate. Of such binders, those containing 50% by mass or more (more preferably 80% by mass or more, and even more preferably 90% by mass or more) of an acrylic polymer compound can be preferably used. A particularly preferred example is a binder that is substantially 100% composed of an acrylic polymer compound.

[0036] In addition, such an acrylic polymer compound can be commercially available. Although not particularly limited, suitable examples of such an acrylic polymer compound include AP-60L, AP-80, AP-96, AP-360, AP368, ES-37, ES-64, ES-85, ES-232, ES-650, SA-200, HS-531, ESZ-4366, FK-285, FK-433, FK-854, and FK-4300 manufactured by Japan Coating Resin Co., Ltd., and WB4101 (all trade names) manufactured by Polymer Innovations Co., Ltd. The binder may be, for example, 1 part by mass or more, more preferably 5 parts by mass or more or 7 parts by mass or more, and may be 15 parts by mass or less, 12 parts by mass or less, or 10 parts by mass or less, based on 100 parts by mass of the main raw material.

[0037] The plasticizer mainly penetrates between the molecules of the binder polymer, weakening the intermolecular forces of the polymer and facilitating the movement of each molecular chain, thereby preventing the polymer from being regularly oriented. As a result, the plasticizer is a compound that has the function of imparting flexibility to the polymer even at or below the glass transition point. In roll molding, the plasticizer is also preferable in that it increases the elasticity of the polymer, thereby improving moldability, such as making it easier to remove the molded sheet from the roll. As the plasticizer, one that is not decomposed by drying treatment (typically, a heat treatment of about 100°C to 200°C) and is easily decomposed and removed by binder removal treatment (typically, a heat treatment of about 200°C to 600°C) can be preferably used.

[0038] Depending on the combination with the binder (e.g., compatibility), examples of the plasticizer include phthalate ester polymers such as dibutyl phthalate, dioctyl phthalate, ditridecyl phthalate, and derivatives thereof; trimellitic acid ester polymers such as tributyl trimellitate, trioctyl trimellitate, and derivatives thereof; di- and polyglycerin polymers such as diglycerin, polyoxypropylene polyglyceryl ether, polyglycerin, and derivatives thereof; glycerin fatty acid ester polymers such as glycerin fatty acid ester monoglyceride, polyglycerin fatty acid ester, sorbitan fatty acid ester, propylene glycol fatty acid ester, and derivatives thereof; glycol ether polymers such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, ethylene glycol isopropyl ether, and derivatives thereof; epoxy polymers such as epoxidized soybean oil, epoxidized linseed oil, and derivatives thereof; etc. can be suitably used.

[0039] As described above, these plasticizers penetrate into the gaps of the polymer and maintain an amorphous state even below the glass transition point. Therefore, it is preferable that the plasticizer has a bulky side chain that can be a steric hindrance. For example, the plasticizer is preferably one having one or more branched chains (e.g., primary or higher), and more preferably one having two or more branched chains (e.g., secondary or higher). The side chain contained in the polymer constituting the plasticizer may be any organic group, for example, an organic group containing a hydrocarbon group, an alkoxy group, a (meth)acrylic group, an epoxy group, an acyl group, an ester group, a mercapto group, a carbonyl group, an ether bond-containing group, or the like. Any one of these may be used, or two or more may be used in combination.

[0040] The amount of the plasticizer may be, for example, 0.1 parts by mass or more, more preferably 0.5 parts by mass or more or 1 part by mass or more, and may be 5 parts by mass or less, 4 parts by mass or less, or 3 parts by mass or less, based on 100 parts by mass of the main raw material.

[0041] As the dispersant, for example, a carboxylic acid-based polymer surfactant can be preferably used. As the release agent, for example, fatty acid calcium and polyolefin can be preferably used. When these additives are used, the amount of the additives added may be adjusted so that, when the main raw material is taken as 100 parts by mass, the total amount of the auxiliary raw materials is, for example, 5 parts by mass or more, 7 parts by mass or more, typically 10 parts by mass or more. In addition, it is preferable that the total amount of the auxiliary raw materials is, for example, 16 parts by mass or less, less than 16 parts by mass, typically 15.5 parts by mass or less.

[0042] The granulation method of the main raw material and auxiliary raw material is not particularly limited, and may be, for example, either wet granulation or dry granulation. Specific examples of the granulation method include rolling granulation, fluidized bed granulation, stirring granulation, compression granulation, extrusion granulation, crushing granulation, and spray drying (spray granulation). From the viewpoint of easier handling of finer raw material powder, a preferred example is a wet granulation method such as spray granulation. According to the spray granulation method, for example, a raw material slurry containing the main raw material and auxiliary raw material can be sprayed in droplets and dried to prepare a granulated powder. Various conventionally known stirring and mixing devices such as a ball mill, mixer, disperser, and kneader can be appropriately used to prepare the raw material mixture. For example, a homogeneous raw material mixture can be prepared by feeding the main raw material and auxiliary raw material into a stirring and mixing device at any timing and stirring and mixing at a stirring speed of 50 rpm to 300 rpm for 0.5 to 1 hour. The order in which the raw materials are fed into the device is not particularly limited, and for example, all the materials may be fed at once, or may be fed in several batches. Although the solvent for preparing the raw material slurry is not particularly limited, it is preferable to use water from the viewpoint of reducing the environmental load. The temperature of the spray drying is preferably a temperature at which the dispersion medium can be completely removed without deteriorating the binder component. The spray drying temperature is, for example, 150°C or higher and 200°C or lower, typically 180°C or higher and 200°C or lower.

[0043] The size of the granulated powder is not strictly limited. The average particle diameter of the granulated powder may be, for example, about 10 μm or more, 15 μm or more, 20 μm or more, or 30 μm or more, depending on the average particle diameter of the primary particles. The average particle diameter of the granulated powder may be, for example, about 200 μm or less, 150 μm or less, 100 μm or less, or 80 μm or less. The average particle diameter of the granulated powder is also determined based on the particle size distribution on a volume basis measured by a particle size distribution measurement based on a general laser diffraction / light scattering method, and is ... general laser diffraction / light scattering method, and is determined based on the particle size distribution measurement based on the general laser diffraction / light scattering method. 50 It is also called the particle size or median size.

[0044] [Green Sheet] The green sheet disclosed herein is an unsintered porous electrode that can be sintered to produce a porous electrode. The green sheet is formed into a sheet shape by uniformly mixing the above-mentioned main raw material and auxiliary raw material. In other words, the green sheet includes the main raw material containing the above-mentioned electrode constituent material and pore-forming material, and the auxiliary raw material containing a binder and a plasticizer as organic components other than the pore-forming material. The green sheet is typically a compression molded body obtained by compression molding (e.g., uniaxial compression molding, typically roll rolling) the above-mentioned granulated powder.

[0045] The thickness of the green sheet is not particularly limited and may be, for example, 2000 μm or less, 1000 μm or less, 500 μm or less, etc. The thickness of the green sheet may be 20 μm or more, 50 μm or more, 100 μm or more, etc. The thickness of the green sheet is the arithmetic average value when the dimension in the thickness direction perpendicular to the surface of the green sheet is measured at five or more points.

[0046] As described above, this green sheet is formed by compressing and molding the granulated powder of the main raw material and the auxiliary raw material. Therefore, uneven distribution due to the specific gravity of the main raw material and the auxiliary raw material in the thickness direction is unlikely to occur. Therefore, when this green sheet is divided equally into two layers 10a and 10b in the thickness direction, as shown in FIG. 2, the difference in the content of the auxiliary raw material in the two layers 10a and 10b is small or can be homogeneous to the extent that there is almost no difference. For example, when comparing the contents Pa and Pb of the auxiliary raw material in the two layers 10a and 10b, the difference |Pa-Pb| (indicating an absolute value) may be 15% or less of the content of the auxiliary raw material in the entire green sheet, and typically may be 10% or less, 5% or less, or 3% or less. The difference in the content of the auxiliary raw material may be understood as, for example, the difference in the content of the binder, the difference in the content of the plasticizer, or the like. The green sheet disclosed herein is preferably prepared so that the porosity, as determined by the Archimedes method or weight measurement as described in the Examples below, is 3% or less, and more preferably 2% or less.

[0047] The green sheet has a moderately high elasticity and is not easily stretched or deformed by tensile stress. The elasticity of the green sheet is not too high, and the resistance to bending deformation is not easily lost. As a result, the green sheet disclosed herein has improved handling properties during cutting, transport, removal from the substrate, and the like. Such a green sheet is prepared so that the tensile storage modulus at 30°C (sometimes simply referred to as storage modulus) is 60 MPa or more and 350 MPa or less. From the viewpoint of suppressing undesired deformation, the tensile storage modulus may be, for example, 75 MPa or more, 100 MPa or more, 120 MPa or more, 130 MPa or more, 140 MPa or more, 150 MPa or more, or 200 MPa or more. However, a tensile storage modulus that is too high is undesirable in that it leads to a decrease in folding resistance. The tensile storage modulus may be 325 MPa or less, 300 MPa or less, 275 MPa or less, or 250 MPa or less. The tensile storage modulus can be measured in accordance with JIS K7244-4: 1988. Specifically, the tensile storage modulus can be measured by the method exemplified in the examples described later.

[0048] Although this green sheet is manufactured by compression molding, the compressive stress applied to the pore-forming material is suitably relaxed by the high elasticity as described above, and the compression deformation of the pore-forming material, which is relatively soft among the main raw materials, can be suppressed. For example, the cross-sectional shape of the pore-forming material contained in the green sheet is not easily deformed in the direction of compression molding. As a result, the pores confirmed in the sintered body obtained by sintering this green sheet are also not easily crushed. For example, when spherical resin beads are used as the pore-forming material, the pore-forming material in the green sheet maintains its spherical shape, thereby suppressing the occurrence of anisotropy in the physical properties of the green sheet. For example, the average ellipticity in the cross-sectional shape of the pores confirmed in the sintered body is maintained at 0.6 or more. The average ellipticity can typically be 0.6 or more, 0.7 or more, for example, 0.8 or more, 0.85 or more, or 0.9 or more.

[0049] Such a green sheet can be realized as one having both appropriate tensile strength and tensile breaking strain. The tensile strength of the green sheet may be, for example, 0.55 MPa or more, 0.6 MPa or more, 0.65 MPa or more, for example, 0.7 MPa or more, 0.75 MPa or more, 0.8 MPa or more. The tensile breaking strain may be, for example, 4% or more, 5% or more, 6% or more, for example, 7% or more, 8% or more, 9% or more, 10% or more.

[0050] [Green sheet manufacturing method] The method for producing the green sheet is not particularly limited, but it can be preferably obtained by compression molding (for example, uniaxial compression molding, typically roll rolling) of the granulated powder. As an example, it can be preferably produced by a roll molding machine 5 shown in FIG. 1. This roll molding machine 5 is roughly equipped with a storage tank 1 for storing the raw material mixture 1a and a pair of rolls 2. The storage tank 1 is a container for storing the raw material mixture 1a. The granulated powder disclosed herein is used as the raw material mixture 1a. The storage tank 1 is also equipped with a feeder 1b at its bottom, and is configured to continuously supply a certain amount of the raw material mixture 1a from the discharge port of the feeder 1b between the pair of rolls 2. The feeder 1b is not particularly limited as long as it is excellent in quantitative supply, and various feeders such as a screw type, a vibration type, and a flow type can be appropriately adopted.

[0051] Although the conditions for roll molding vary depending on the roll molding machine used, it is preferable to perform roll molding within a temperature range in which the binder used in preparing the granulated powder softens. The gap between the pair of rolls can be appropriately adjusted so as to obtain a green sheet of a desired thickness. Preferably, the temperature of the roll 2 during roll molding is set higher than room temperature. It is more preferable to set the temperature higher than the softening point of the binder contained in the raw material mixture (granulated powder) 1a, for example, 10°C or more higher (e.g., 20°C or more higher) than the softening point of the binder. Specifically, the temperature is usually about 30°C to 200°C, for example, 50°C to 150°C. The press line pressure between the pair of rolls 2 is not particularly limited, but is usually 0.1 kN / cm to 30 kN / cm, for example, 0.5 kN / cm to 10 kN / cm. The forming speed of the green sheet 10G is usually 0.1 m / min to 20 m / min, for example, 0.5 m / min to 10 m / min. According to this embodiment, problems such as warping and deformation are less likely to occur compared to conventional methods, and a homogeneous green sheet 10G can be stably formed. The distance between the pair of rolls 2 is not particularly limited and can be adjusted appropriately depending on the thickness of the green sheet as the target. The distance between the rolls 2 can be, for example, 50 μm or more (typically 100 μm or more, for example 200 μm or more) and 3000 μm or less (typically 2000 μm or less, for example 1000 μm or less). In the roll forming method, a green sheet 10G having a desired thickness can be easily formed by simply adjusting the distance between the rolls 2.

[0052] [Other aspects] In the above description, the green sheet is used for forming the fuel electrode of SOFC. However, the use of the green sheet is not limited to this, and the green sheet can be used as a green sheet for forming any porous electrode. As an example, the green sheet may be used for forming the fuel electrode of SOFC. In this case, the electrode constituent material may be a known air electrode material powder or a precursor powder of the air electrode material. Typical examples of the air electrode material include lanthanum cobaltite (LaCoO3), lanthanum manganate (LaMnO3), lanthanum ferrite (LaFeO3), and lanthanum nickelate (LaNiO3) perovskite oxides; and samarium cobaltite (SmCoO3) perovskite oxides. Here, for example, the lanthanum cobaltite oxide includes oxides containing La and Co as constituent metal elements, as well as oxides containing one or more metal elements (transition metal elements and / or typical metal elements) other than La and Co. The same is true for lanthanum manganate oxides, lanthanum ferrite oxides, lanthanum nickelate oxides, and samarium cobaltite oxides. Typical examples include Sr-doped LaMnO3 oxides (e.g., La 0.8 Sr 0.2 MnO3), Sr-doped LaCoO3-based oxides (e.g., La 0.6 Sr 0.4 CoO3), Sr- and Fe-doped LaCoO3-based oxides (e.g., La 0.6 Sr 0.4 Co 0.2Fe 0.8 O3). These oxides are so-called mixed electron-oxide ion conductors, and are suitable because they exhibit higher reaction activity (higher catalytic activity) than other perovskite oxides. Any one or more of these can be used without any particular limitation.

[0053] Some examples of the present invention will be described below. However, it is not intended that the present invention be limited to the following examples.

[0054] [Preparation of granulated powder] Comparative Example 1 As main raw materials, nickel oxide powder (NiO, average particle size 0.5 μm), 8 mol% yttria-stabilized zirconia powder (8YSZ, average particle size 0.3 μm), and acrylic beads (average particle size 5 μm) as a pore-forming material were weighed out in a mass ratio of 45.5:45.5:0.9 as shown in Table 1 below. In addition, as auxiliary raw materials, an acrylic binder, a plasticizer (weight average molecular weight 1500), a release agent, and an antifoaming agent were weighed out in amounts of 11.8 parts by mass, 0.9 parts by mass, 2.7 parts by mass, and 0.5 parts by mass, respectively, per 100 parts by mass of the main raw material, as shown in Table 1 below.

[0055] The main raw material and auxiliary raw material were prepared by putting them into a pot mill together with 10 mm diameter pebbles and the same mass of water (dispersion medium) and mixing for 8 hours to prepare a raw material slurry. This raw material slurry was then spray-dried in a spray-drying granulation device to produce the granulated powder of Comparative Example 1. The spraying conditions were adjusted so that the average particle size of the granulated powder was about 30 μm. The drying temperature in the spray drying was about 180 to 200° C., and the dispersion medium contained in the granulated powder was almost 0 mass %.

[0056] Example 1 The composition of the main raw materials was the same as in Comparative Example 1, and the auxiliary raw materials, an acrylic binder, a plasticizer (weight average molecular weight 150), a release agent, and an antifoaming agent, were weighed out in proportions of 5.3 parts by mass, 2.4 parts by mass, 2.6 parts by mass, and 0.3 parts by mass, respectively, when the main raw materials were 100 parts by mass, as shown in Table 1 below. The other conditions were the same as in Comparative Example 1, and spray drying was performed to produce the granulated powder of Example 1.

[0057] Example 2 The composition of the main raw materials was the same as in Comparative Example 1, and the auxiliary raw materials, an acrylic binder, a plasticizer (weight average molecular weight 150), a release agent, and an antifoaming agent, were weighed out in proportions of 5.3 parts by mass, 2.4 parts by mass, 2.6 parts by mass, and 0.3 parts by mass, respectively, when the main raw materials were 100 parts by mass. The other conditions were the same as in Comparative Example 1, and a raw material slurry was prepared and spray-dried to produce a granulated powder of Example 2.

[0058] Example 3 The composition of the main raw materials was the same as in Comparative Example 1, and the auxiliary raw materials, an acrylic binder, a plasticizer (weight average molecular weight 350), a release agent, and an antifoaming agent, were weighed out in proportions of 9.8 parts by mass, 2.3 parts by mass, 2.9 parts by mass, and 0.5 parts by mass, respectively, when the main raw materials were 100 parts by mass, as shown in Table 1 below. The other conditions were the same as in Comparative Example 1, and a raw material slurry was prepared and spray-dried to produce a granulated powder of Example 3.

[0059] Example 4 The composition of the main raw materials was the same as in Comparative Example 1, and the auxiliary raw materials, an acrylic binder, a plasticizer (weight average molecular weight 1500), a release agent, and an antifoaming agent, were weighed out in proportions of 9.5 parts by mass, 2.7 parts by mass, 3.1 parts by mass, and 0.5 parts by mass, respectively, when the main raw materials were 100 parts by mass, as shown in Table 1 below. The other conditions were the same as in Comparative Example 1, and a raw material slurry was prepared and spray-dried to produce a granulated powder of Example 4.

[0060] (Examples 5 to 7) In Examples 5 to 7, rice starch, carbon beads, and polyethylene beads were used instead of acrylic beads as pore-forming materials. The average particle size of these pore-forming materials was the same at 5 μm. The other conditions were the same as in Example 3, and the raw material slurry was prepared and spray-dried to produce the granulated powders of Examples 5 to 7.

[0061] Comparative Example 2 The composition of the main raw materials was the same as in Comparative Example 1, and the auxiliary raw materials, an acrylic binder, a plasticizer (weight average molecular weight 1500), a release agent, and an antifoaming agent, were weighed out in proportions of 8.9 parts by mass, 3.5 parts by mass, 3.1 parts by mass, and 0.5 parts by mass, respectively, when the main raw materials were 100 parts by mass, as shown in Table 1 below. The other conditions were the same as in Comparative Example 1, and a raw material slurry was prepared and spray-dried to produce a granulated powder of Comparative Example 2.

[0062] [Preparation of green sheets] The granulated powder of each example was used to form a sheet using a roll compaction molding device to form a green sheet of each example with a thickness of approximately 0.5 mm. The conditions for roll compaction molding were as follows. The green sheets of each example thus produced were divided into two equal parts in the thickness direction, and the binder content of each layer was measured. It was confirmed that the difference between the binder contents of all the green sheets was 3 mass% or less of the binder content of the entire green sheet, and that the composition was uniform in the thickness direction. Roll temperature: above the softening point of the binder Roll gap: 0.5mm Molding speed: 0.5m / min

[0063] <Storage modulus of green sheet> Tensile storage modulus E' of each green sheet f was measured by dynamic mechanical analysis (DMA) in accordance with JIS K7244-4:1988. First, a test specimen was prepared by processing each green sheet (thickness about 0.5 mm) to a size of about 10 mm x about 40 mm. Then, both ends of the test specimen in the longitudinal direction were clamped between the measurement heads, and a sinusoidal tensile force was applied to the test specimen in the longitudinal direction at a frequency of 1 Hz with a test temperature of 30°C. At this time, the tensile storage modulus E' was calculated from the relationship between the stress applied to the test specimen and the strain of the test specimen. f was calculated and shown in the "storage modulus" column in Table 1 below. In Table 1, when the storage modulus was 60 MPa or more, it was determined that the resistance to strain due to an external force in the tensile direction was sufficient and was marked with "○", and when it was less than 60 MPa, it was determined that the resistance was insufficient and was marked with "×". In addition, the void ratio (%) was calculated based on the actual density obtained by measuring the outer diameter and weight of the test piece for each example and the theoretical density calculated from the blending ratio according to the following formula, and is shown in the corresponding column in Table 1. Porosity (%) = (1-(actual density) / (theoretical density)) x 100 The porosity of all the specimens tested was 3% or less (more precisely, 2% or less), which was considered to be good (○). Some specimens had a porosity of 1% or less.

[0064] <Tensile properties of green sheet> The tensile properties of the green sheets of each example were measured using a tensile tester in accordance with ASDM D638. First, test pieces (approximately 10 mm x 50 mm) were prepared by punching out the green sheets (approximately 0.5 mm thick) of each example with a dumbbell-shaped test piece punching blade. Measurements were performed using a tensile strength tester (Shimadzu Corporation, tabletop tester: EZ-TEST), with both ends of the test piece in the longitudinal direction clamped in a chuck, at a test temperature of 25°C and a constant tensile speed of 1 mm / min. From the relationship between the stress and strain applied to the test piece at this time, the tensile strength σ and tensile fracture strain ε b The test was carried out 10 times, and the average values ​​are shown in Table 1 below. The tensile breaking strain ε bis the tensile strain immediately before the stress decreases to 10% or less of the tensile strength when there is no yield and fracture. In Table 1, when the tensile strength is 0.6 MPa or more, it is judged that the strength against the tensile stress is sufficient and is marked with "○", and when it is less than 0.6 MPa, it is judged that the strength is insufficient and is marked with "×". In addition, when the tensile fracture strain is 4% or more and less than 10%, it is judged that the ductility against the tensile stress is sufficient and is marked with "○", when it exceeds 10%, it is marked with "◎", and when it is less than 4%, it is judged that the ductility is insufficient and is marked with "×".

[0065] <Green sheet folding strength> The folding endurance tensile properties of the green sheets of each example were measured using an MIT testing machine in accordance with JIS P8115:2001. First, the green sheet (thickness about 0.5 mm) of each example was cut into a size of about 10 mm x about 40 mm to prepare a test piece. Then, the upper end of the test piece in the longitudinal direction was fixed to a specified load clamp (9.8 N, deadweight method), and the other end was fixed to a folding clamp. While pulling the test piece with a specified load, the test piece was repeatedly folded up to 10 times under the conditions of a bending angle of 135° left and right and a bending speed of 175 times / min. The curvature radius R of the folding surface of the folding clamp was set to 6 mm. Then, the folding endurance was calculated from the number of times of reciprocating folding (folding endurance number) until the test piece broke, and is shown in Table 1 below. In Table 1, when the test piece did not break after 10 times of folding, it was judged that the folding endurance was sufficient, and "○" was added, and when the number of times of folding was less than 10 times, it was judged that the folding endurance was insufficient, and "×" was added. The folding endurance is the common logarithm of the number of reciprocating foldings until the test piece breaks.

[0066] <Porosity characteristics of fired sheet> The green sheets of each example were fired to obtain fired bodies, and the properties of the pores contained in the fired bodies were evaluated. Specifically, first, the green sheet of each example was cut to an appropriate size, placed on a flat setter, and heated at 360°C for 20 hours to degrease it. After that, it was sintered in a sintering furnace at a maximum temperature of 1300°C for 7 hours to obtain a thin plate-shaped sintered body. The porosity and average pore diameter of the fired bodies of each example thus obtained were measured by mercury intrusion porosimetry (using a commercially available general mercury porosimeter), and the results are shown in Table 1 below.

[0067] In addition, a cross section perpendicular to the surface of each sintered body (cross section along the thickness direction) was observed with a scanning electron microscope (SEM), and a cross-sectional SEM image with a magnification of about 3000 times was prepared. The cross-sectional SEM image was then analyzed to calculate the average ellipticity of the pores seen in the cross section. Here, the ellipticity is calculated by drawing a circumscribing circle and an inscribing circle for an independent pore that is not a continuous pore seen in the cross section, and calculating the ratio of the minor axis to the major axis, with the diameter of the circumscribing circle as the major axis and the diameter of the inscribing circle as the minor axis. The average ellipticity is the arithmetic mean value of the ellipticities calculated for 50 or more pores. The results are shown in Table 1 below. In Table 1, when the average ellipticity is 0.7 or more, the pores are not crushed and the sintered body is isotropic, and when the average ellipticity is less than 0.7, the pores are crushed and the sintered body is anisotropic, and the average ellipticity is added with "○". For reference, cross-sectional SEM images obtained for the sintered bodies of Example 3 and Comparative Example 2 are shown in FIGS. 3(A) and (B), respectively.

[0068] [Table 1]

[0069] (evaluation) In Comparative Example 2, the ratio of the organic auxiliary raw material is slightly increased compared to the typical raw material blend used when forming a green sheet by the conventional roll compaction method. In the molding by the roll compaction method, a compressive stress is applied in the thickness direction of the green sheet. As can be seen from the fact that the pores in the sintered body are flattened in the thickness direction as shown in FIG. 3(B), the pore-forming material is compressed and deformed in the thickness direction in the green sheet by the roll compaction method, which causes anisotropy in the properties of the green sheet. In order to give the sintered body effective porosity, the pore-forming material has a larger particle size than other powder raw materials, but the flat shape of such a large particle pore-forming material weakens the bond of the material particles in the direction perpendicular to the thickness direction of the green sheet, and for example, the storage modulus of the green sheet in the blend of Comparative Example 2 is about 50 MPa. Although this is higher than the storage modulus (less than 50 MPa) of green sheets formed by the doctor blade method using a conventional slurry raw material containing a solvent, such green sheets are prone to stretching and deformation or tearing during transportation, leaving room for improvement in terms of handling.

[0070] Here, for example, as can be seen from the comparison of Comparative Example 1, Examples 1 to 4, and Comparative Example 2, it was found that the storage modulus of the green sheet formed by the roll compaction method can be significantly changed by adjusting the blending of the organic components, which are the auxiliary raw materials. In addition, it was found that as the storage modulus of the green sheet increases, the collapse of the pores in the fired body is improved, and the pore-forming material maintains a cross-sectional shape closer to a circle after roll compaction. This is thought to be because the storage modulus of the granulated powder, which is the raw material for compaction, is also increased, and as a result, it is possible to suitably prevent the concentration of compression force on the pore-forming material with a larger particle size during roll compaction.

[0071] From the above, it was found that the storage modulus of the green sheet can be significantly increased by adopting the roll compaction method and adjusting the blending of the organic components of the green sheet raw material. In other words, it was found that by adjusting the blending of the organic components of the green sheet raw material, a green sheet with high elasticity, which is difficult to elongate and deform under the same external force, and excellent handling properties can be obtained. It was confirmed that the storage modulus of the green sheet can be significantly increased, for example, by slightly increasing the amount of binder and slightly decreasing the amount of plasticizer, or by increasing the molecular weight of the plasticizer while decreasing the amount of binder, compared to the conventional method. As can be seen from the comparison between Comparative Example 1 and Examples 1 and 2, it is not only the ratio of the auxiliary raw material to the main raw material that affects the adjustment of the storage modulus. It was confirmed that the storage modulus of the green sheet can be increased to 60 MPa or more, for example, 70 MPa or more.

[0072] Among the physical properties of the green sheet, the tensile strength shows a similar tendency to the storage modulus with respect to the change in the composition of the organic components, but the tensile breaking strain and folding endurance show different tendencies. In other words, it was found that the higher the storage modulus and tensile strength, the lower the folding endurance. This is thought to be because the more elastic the green sheet is, the lower the ductility becomes and the stronger the rigidity becomes, which leads to a lower resistance to bending. Considering the folding endurance of the green sheet, it is recommended that the storage modulus be approximately 400 MPa or less, for example, 350 MPa or less.

[0073] Although specific examples of the present invention have been described above in detail, these are merely examples and do not limit the scope of the claims. The technology described in the claims includes various modifications and changes to the specific examples exemplified above. For example, the combination of the main raw material and the auxiliary raw material in the embodiment exemplified above is merely an example, and it goes without saying that materials other than those mentioned above can be used. [Explanation of symbols]

[0074] 1 Storage tank 1a Raw material mixture 1b Feeder 2 rolls 5. Roll forming machine 10G Green Sheet

Claims

1. A solvent-free green sheet used to form a porous electrode, A main raw material including at least a conductive material and an electrolyte material as electrode constituent materials, and including acrylic beads made of an acrylic resin as a pore-forming material, the average particle diameter of the pore-forming material being 2 to 20 times the average particle diameter of the electrode constituent materials; an auxiliary material including an organic component other than the pore-forming material, and a binder and a plasticizer; Including, A green sheet having a tensile storage modulus at 30°C of 60 MPa or more and 350 MPa or less.

2. When the pore-forming material is a spherical powder, 2. The green sheet according to claim 1, wherein an average ellipticity of a cross-sectional shape of pores confirmed in a sintered body obtained by sintering the green sheet is 0.6 or more.

3. 3. The green sheet according to claim 1, wherein the tensile strength is 0.6 MPa or more and the tensile breaking strain is 4% or more.

4. 4. The green sheet according to claim 1, wherein the folding endurance is 1 or more.

5. The green sheet according to any one of claims 1 to 4, wherein the ratio of the auxiliary material to the main material is 10 parts by mass or more and 17 parts by mass or less when the main material is 100 parts by mass.

6. 6. The green sheet according to claim 1, wherein the binder contains an acrylic polymer compound.

7. The green sheet according to any one of claims 1 to 6, wherein the plasticizer comprises a diglycerin-based polymer.

8. The green sheet according to any one of claims 1 to 7, wherein the loss on drying at 105°C is 1 mass% or less.

9. A granulated powder for forming the green sheet according to any one of claims 1 to 8, A main raw material including at least a conductive material and an electrolyte material as electrode constituent materials, and including acrylic beads made of an acrylic resin as a pore-forming material, the average particle diameter of the pore-forming material being 2 to 20 times the average particle diameter of the electrode constituent materials; an auxiliary material including an organic component other than the pore-forming material, and a binder and a plasticizer; is granulated, The average particle size is 10 μm or more and 200 μm or less, The following conditions: Roll temperature: equal to or higher than the softening point of the binder; Roll gap: 0.05 to 3.0 mm; Molding speed: 0.5m / min; The granulated powder is configured so that when a green sheet is formed by compressing the green sheet to a void ratio of 3% or less by the above-mentioned method, the tensile storage modulus of the sheet at 30° C. is 60 MPa or more and 350 MPa or less.

Citation Information

Patent Citations

  • Electrostriction type actuator device and fuel injector for diesel engine using said device

    JP1987058882A

  • Composition for dielectric layer, green sheet, dielectric-layer-formed substrate and method of manufacturing the same

    JP2007039288A

  • Ceramic green sheet, laminated electronic component, and manufacturing method thereof

    JP2007123427A

  • Green sheet for solid oxide fuel cell and method of manufacturing the same

    JP2016149314A

  • Method for manufacturing ceramic green laminate for solid oxide fuel cell, method for manufacturing half cell for solid oxide fuel cell, method for manufacturing single cell for solid oxide fuel cell, ceramic green laminate for solid oxide fuel cell, half cell for solid oxide fuel cell, and single cell for solid oxide fuel cell

    JP2016207384A